2016
DOI: 10.1063/1.4966965
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic dynamics in intense continuous wave laser fields and real-time observation of the associated wavepacket bifurcation in terms of spectrogram of induced photon emission

Abstract: We propose a theoretical principle to directly monitor the bifurcation of quantum wavepackets passing through nonadiabatic regions of a molecule that is placed in intense continuous wave (CW) laser fields. This idea makes use of the phenomenon of laser-driven photon emission from molecules that can undergo nonadiabatic transitions between ionic and covalent potential energy surfaces like Li F and LiF. The resultant photon emission spectra are of anomalous yet characteristic frequency and intensity, if pumped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Further novel methods have been introduced, such as attosecond stimulated X-ray Raman spectroscopy [147], time-resolved fluorescent spectroscopy [148], ultrafast electron diffraction technique [149], and so on. We also found that the wavepacket bifurcation can be directly observed not only by pump-probe technique by means of pulse lasers but with induced photoemission spectroscopy from molecules placed under a CW laser [150].…”
Section: Experimental Observation Of Bifurcation and Merge Of The Qua...mentioning
confidence: 76%
“…Further novel methods have been introduced, such as attosecond stimulated X-ray Raman spectroscopy [147], time-resolved fluorescent spectroscopy [148], ultrafast electron diffraction technique [149], and so on. We also found that the wavepacket bifurcation can be directly observed not only by pump-probe technique by means of pulse lasers but with induced photoemission spectroscopy from molecules placed under a CW laser [150].…”
Section: Experimental Observation Of Bifurcation and Merge Of The Qua...mentioning
confidence: 76%
“…Unfortunately, however, j el ( r , Q , t ) demonstrated in Figure is not experimentally observable even though conceptually relevant. Conversely, Mizuno et al have shown that if a molecule of nonadiabatic electron transfer like LiF is placed under a CW laser, there exist photon emission signals that directly reflect the decoherence between two bifurcating wavefunctions …”
Section: Flux Analysismentioning
confidence: 99%
“…We also have found characteristic phenomena emerging from the electron transfer in alkali halides, with use of the full quantum mechanical methodology both for electrons and nuclei. The phenomena revealed include (i) direct observation of wavepacket bifurcation associated with nonadiabatic transitions in terms of femtosecond time‐resolved photoelectron spectroscopy, (ii) optical controllability of nonadiabatic transitions using the dynamical Stark effect or by symmetry braking of symmetry‐allowed conical intersection, (iii) anomalous photon emission by applying CW lasers on the intramolecular electron transfer systems, and (iv) laser‐assisted confinement of quantum wavepackets by the CW laser induced Floquet states coupled with the intrinsic nonadiabatic interactions, and so on.…”
Section: Introductionmentioning
confidence: 99%